PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT MITRA KOLEKSI MANDIRI TANGERANG BANTEN - Yuni Kartika; Asep Suherman (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to determine the Effect of Work Motivation and Work Discipline on Employee Performance at PT Mitra Koleksi Mandiri Tangerang Banten both partially and simultaneously. This type of research uses quantitative methods. The sampling technique uses saturated samples of 83 respondents. Data analysis techniques use data instrument tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients, and hypothesis tests. The results of the analysis show: Work motivation partially has a significant effect on employee performance with a simple linear regression equation Y = 4.171 + 0.868X1. The correlation coefficient value of 0.900 and the determination coefficient of 81% means it has a very strong level of relationship. This is proven by the hypothesis test obtained t count> t table (18.572> 1.990) and strengthened by a significant value <0.05 (000<0.05). Work discipline partially has a significant effect on employee performance with a simple linear regression equation Y = 1.832 + 0.927X2. The correlation coefficient value of 0.943 and the determination coefficient of 88.8% means that it has a very strong level of relationship. This is proven by the hypothesis test which obtained tcount > ttable (25.390 > 1.990) and is strengthened by a significant value of <0.05 (000 <0.05). The results of the study showed that work motivation and work discipline simultaneously had a significant effect on employee performance with a multiple regression equation of Y = 1,486 + 0.181X1 + 0.756X2. The correlation value of 0.945 and the coefficient of determination of 89.1% means that employee performance is influenced by work motivation and work discipline 89.1% while the remaining 10.9% is influenced by other factors. This is proven by the hypothesis test obtained F count value > F table (335.184 > 3.11) and is strengthened by a significant value <0.05 (000 <0.05). Thus, it is proven that H0 is rejected and Ha is accepted.